ANALISIS ECONOMIC EXPOSURE DAN DETERMINANNYA PADA PERUSAHAAN YANG LISTING DI BURSA ELEK JAKARTA (AGUSTUS 1997 - JUNI 2003) - Hastuti, Fitri; Hady, Hamdy (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2004)
The aim of this research is to examine the elasticity and the sign of economic exposure of listed companies in period sample and subperiod sample, and also to analyze the potential factors that determine the elasticity of economic exposure. To achieve those goals, we use two linear regression equations with Ordinary Least Square (OLS) method. The first regression called first stage regression use time series data from August 1997 until June 2003. The second one called second stage regression use cross section data of sample 35 companies. The first stage regression result shows the elasticity and the sign of economic exposure of 35 companies during sample period of August 1997 until June 2003 and also in 3 sub-period samples. The second stage regression shows that economic exposure elasticity is significantly influenced by firm size, the company's operational area, the percentage of asset in foreign currency relative to total asset, and the percentage of debt in foreign currency relative to total debt. While traded sector and source of financing don't influence economic exposure elasticity significantly.